Chinese Guidelines for the Management of Acne Vulgaris: 2019 Update# - Acne Group, Combination of Traditional and Western Medicine Dermatology; Acne Group, Chinese Society of Dermatology; Acne Group, Chinese Dermatologist Association; Acne group, Dermatology Committee, Chinese Non-government Medical Institutions Association (Wolters Kluwer Health, 2019)
Abstract. The first Chinese guidelines for the management of acne vulgaris was developed and published in 2008 and updated in 2015. With the acquisition of new evidence-based data and the development of new medicines and techniques, the guidelines should be updated regularly. Here, the Chinese guidelines for the treatment of acne vulgaris 2019 update was developed based on the feedback of dermatologists applying in previous version, advances in acne research, as well as the opinions of the experts.